EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Seri Madona Siregar; Eva Yanti Siregar; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
Abstract This study aims to know whether there is the effectiveness of using Reciprocal Teaching learning model on students’ mathematical communication ability on the topic solid figure at the eighth grade students of MTs. Al-Mukhtariyah Sunagi Dua Portibi. The research was conducted by applying experimental method (one group pretest post test design) with 30 students as the sample and they were taken by using simple random sampling technique from 130 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using reciprocal teaching learning model was 3.00 (good category) and (b) the average of students’ solid figure achievement before using reciprocal teaching learning model was 52.38 (fair category) and after using reciprocal teaching learning model was 83.33 (very good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 22), the result showed significant value was less than 0.05(0.000<0.05). It means reciprocal teaching learning model was effective used on students’ mathematical communication ability on the topic solid figure at the eighth grade students of MTs. Al-Mukhtariyah Sunagi Dua Portibi. Keywords: reciprocal teaching learning model, students’ mathematical communication ability